The role of distances in requirements communication: a case study. Issue 1 (March 2017) - Bjarnason, Elizabeth; Sharp, Helen
Abstract Requirements communication plays a vital role in development projects in coordinating the customers, the business roles and the software engineers. Communication gaps represent a significant source of project failures and overruns. For example, misunderstood or uncommunicated requirements can lead to software that does not meet the customers' requirements, and subsequent low number of sales or additional cost required to redo the implementation. We propose that requirements engineering (RE) distance measures are useful for locating gaps in requirements communication and for improving on development practice. In this paper, we present a case study of one software development project to evaluate this proposition. Thirteen RE distances were measured including geographical and cognitive distances between project members, and semantic distances between requirements and testing artefacts. The findings confirm that RE distances impact requirements communication and project coordination. Furthermore, the concept of distances was found to enable constructive group reflection on communication gaps and improvements to development practices. The insights reported in this paper can provide practitioners with an increased awareness of distances and their impact. Furthermore, the results provide a stepping stone for further research into RE distances and methods for improving on software development processes and practices.